2008
DOI: 10.1159/000167879
|View full text |Cite
|
Sign up to set email alerts
|

Clock Drawing Test in Mild Cognitive Impairment: Quantitative Analysis of Four Scoring Methods and Qualitative Analysis

Abstract: Background: The role of the clock drawing test (CDT) as a screening tool for dementia has been evaluated. However, studies focusing on mild cognitive impairment (MCI) are still lacking. The purpose of this study was to verify the validity of the CDT as a screening method for MCI. Methods: 524 subjects aged 60 years and older were recruited in the community. Of these, 241 were diagnosed as not cognitively impaired (NCI) and 224 were classified as MCI. The CDT was scored according to the Freedman, Rouleau, Todd,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 45 publications
4
36
0
Order By: Relevance
“…Furthermore, the relationship between the activity of the neuromuscular and central nervous systems has been shown to be very strong [16,17], and gait variability increases in adults with cognitive impairment [15,18]. Consequently, dual task walking has become the standard measure of the relationship between cognitive ability and gait [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the relationship between the activity of the neuromuscular and central nervous systems has been shown to be very strong [16,17], and gait variability increases in adults with cognitive impairment [15,18]. Consequently, dual task walking has become the standard measure of the relationship between cognitive ability and gait [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The CDT has a high sensitivity and specificity for the detection of Alzheimer’s dementia (AD) [10], but a poor sensitivity for the detection of amnestic MCI (aMCI) [11,12,13,14,15,16] that is assumed to reflect the prodromal stage of AD [17]. Cognitive processes involved in CD seem to be impaired quite late when AD has already manifested.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the CDT requires different cognitive abilities including auditory and visual comprehension, concentration, visuospatial abilities, abstract conceptualization, and executive control (Shulman, 2000). However, the findings concerning the CDT's ability to differentiate between subjects with and without MCI are rather inconsistent (Lee et al, 2008;Pinto and Peters, 2009;Ehreke et al, 2010). For example, Yamamoto et al (2004) found that the CDT has utility to screen for MCI, whereas Lee et al (2008) did not recommend the use of the CDT as a screening instrument for MCI.…”
Section: Introductionmentioning
confidence: 99%